1974
DOI: 10.1002/1097-0142(197403)33:3<619::aid-cncr2820330305>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell leukemia: Detailed studies and response to therapy

Abstract: A case of plasma cell leukemia (PCL) was shown by immunoelectrophoretic and immunofluorescent studies to be producing kappa light chains. Cyto‐chemical staining of the cells revealed strong β‐glucuronidase, oil red 0, and acid phosphatase positivity. Electron microscopy demonstrated various stages in plasma cell development. A good partial remission was obtained following a combination regimen of cyclophosphamide, vincristine, cytosine arabinoside, and prednisone (COAP). Intermittent high dosage melphalan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Shaw et al16 obtained a good partial response following a regimen of cyclophosphamide, vincristine, cytosine arabinoside and prednisolone (COAP) and later high dosage melphalan and prednisolone.Their patient survived for 13 months and Lishner et al8 using COAP achieved a survival of 22 months.Cyclophosphamide12'14 alone, or in combination with prednisolone12'13 has effected survival of up to 4 years and in one case doxorubicin successfully controlled subcutaneous tumour nodules. In our patient general debility precluded this being used.…”
mentioning
confidence: 99%
“…Shaw et al16 obtained a good partial response following a regimen of cyclophosphamide, vincristine, cytosine arabinoside and prednisolone (COAP) and later high dosage melphalan and prednisolone.Their patient survived for 13 months and Lishner et al8 using COAP achieved a survival of 22 months.Cyclophosphamide12'14 alone, or in combination with prednisolone12'13 has effected survival of up to 4 years and in one case doxorubicin successfully controlled subcutaneous tumour nodules. In our patient general debility precluded this being used.…”
mentioning
confidence: 99%
“…Skadberg et al (32) reported the sudden death of a patient with multiple myeloma and cardiac amyloidosis who developed complete heart block. Plasma cell leukemia may arise either as a terminal manifestation in an individual with an established diagnosis of myeloma or as a de novo acute leukemia and typically follows the fulminant course characteristic of the other acute leukemias (3)(4)(5)(6)(7)33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Median survival was 2 months, with only 3 patients living at l year [9]. Various other series have reported a median survival of 6 months [3,6,10,11].…”
Section: Discussionmentioning
confidence: 99%